Peningkatan Kemandirian Santri Melalui Kepemimpinan Transformasional Kiai - M. Amirul Mukhlasin Al Hariri; Mochammad Syafiuddin Shobirin (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
This article seeks to explain how the transformational leadership of the kiai at the Al Ikhlas Bahrul Ulum Tambakberas Jombang Islamic boarding school can increase the independence of the students. In addition, this study also aims to identify the factors that support and hinder the increase in the independence of the students through the transformational leadership of the kiai in the Islamic boarding school. This research uses a case study approach and qualitative research methods. The research location was carried out at the Al Ikhlas Bahrul Ulum Tambakberas Islamic boarding school, Jombang. Data collection techniques include participant observation, interviews, and documentation. Data were analyzed using data reduction techniques, data presentation, and data verification. The validity of the data is tested through credibility, transferability, dependability, and confirmability. The data analysis techniques used include data reduction, data presentation, and data verification, as well as testing the validity of the data through credibility, transferability, dependability, and confirmability. The results of the study show that the Kiai at the Islamic Boarding School has made efforts to increase the independence of the students through transformational leadership that implements leadership functions such as ideal influence, intellectual stimulation, individual consideration, and inspiring motivation. Supporting factors for increasing the independence of students include a conducive environment, character education, skills education, participation of students in Islamic boarding schools activities, and family support. While the inhibiting factors include the lack of motivation and interest in learning from students, the lack of support and guidance from the family, and the lack of understanding of how to learn independently.